Teaching Vocabulary Through Morphological Analysis At The Second Year Students Of MTs PPUW Benteng - sam hermansyah; Aisyah Aisyah; Syamsu Tang; Usman M; Umrah Umrah (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2021)
The objective of the research is to find whether or not the use of morphological analysis can improve the student vocabularu mastery.The research was applied quasi-experimental design . It involved two groups, The experimental group and the control group. The population of this research was the second year students in academic year 2014-2015 of MTS PPUW Benteng. It consist of 7 classes. The total number of population is178 students, The researcher choesestwo classes as simple .Finally, The researcher selected VIII/D as the experimental group and VIII/E as the control group. VIII.D consist of 16 students and VIII.E consist of 16 students so the total sample of the research is 32 students The researcher applied morphological analysis on the sxperimental group and for the contol group the student tought using conventional technique . There were two Thenques of data collecting applied in this study , They were test . The test is used to compare students vocabulary achievements,The application of morphological analysis anhanced the students ability to vocabulary mastery in the second year students of MTS PPUW Benteng . The achievement in vocabulary mastery of the students who applied morphological analysis and those who did not apply morphological analysis had sighnficant difference . It was oroved by the mean score in post test of experimental group was bigher than the mean score of control groupn (79.37-66.87) and the t,test value on post test was bigher than t-table(3.363>2.042)Based on the data above the researcher cocluded that using morphological analysis increase students vocabulary mastery.